2017
DOI: 10.1038/s41598-017-01029-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of peanut Arachis hypogaea roots to the presence of beneficial and pathogenic fungi by transcriptome analysis

Abstract: Entomopathogenic fungus Metarhizium anisopliae obtain survival benefit meanwhile promote the nutrient absorption of root as an endophyte. However, little is known concerning molecular mechanisms in the process. We performed the transcriptome sequencing of A. hypogaea roots inoculated M. anisopliae and pathogenic Fusarium axysporum, respectively. There were 81323 unigenes from 132023 transcripts. Total 203 differentially expressed genes (DEGs) respond to the two fungi, including specific 76 and 34 DEGs distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Alfalfa cultivars were used from each of the four treatments, RNA extraction, library construction and sequencing were carried out as described previously [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfalfa cultivars were used from each of the four treatments, RNA extraction, library construction and sequencing were carried out as described previously [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…All the downstream analyses were based on clean data with high quality, and the methods for sequence reads and mapping could be referenced as Hao et al [ 27 ]. The left.fq and right.fq were used for the transcriptome assembly [ 27 ], and seven databases including Nt (NCBI non-redundant nucleotide sequences), Nr (NCBI non-redundant Protein sequences), Pfam (Protein family), KO (KEGG Ortholog database) and GO (Gene Ontology), KOG/COG (Clusters of Orthologous Groups of proteins), Swiss-Prot (a manually annotated and reviewed protein sequence database) were used for gene function annotation [ 27 ]. Data for each sequenced library was analyzed using BLAST with a cutoff E-value of 10 − 5 .…”
Section: Methodsmentioning
confidence: 99%
“…There were also several candidate genes identified to be associated with only one trait in the present study. Among these, Feruloyl CoA ortho-hydroxylase 1-like that play a role in oxidation-reduction process (Hao et al, 2017) were related to M7405 (Table 4). Protein PHR1-LIKE 2-like, which is responsible for stresses response (Li et al, 2016), was associated with M6734 (Table 9).…”
Section: Putative Candidate Genesmentioning
confidence: 99%
“…This technique is widely used for understanding host-pathogen interaction as well as elucidating plant defense pathways [13,14]. Moreover, it has been successfully used to unfold various developmental pathways [15], oil accumulation pathways [16], and in response to biotic [17] and abiotic stimuli in peanut [18,19]. An RNA-Seq transcriptome analysis of Brassica infected with Sclerotinia sclerotiorum revealed that the genes involved in pathogen recognition, MAPK signaling cascade, regulation of WRKY transcription factors, and jasmonic acid and ethylene signaling pathways, impart resistance [20,21].…”
Section: Introductionmentioning
confidence: 99%